2009
DOI: 10.1186/1749-8090-4-62
|View full text |Cite
|
Sign up to set email alerts
|

Coronary arteriovenous fistulas in the adults: natural history and management strategies

Abstract: Objective: To describe aspects of the natural history and pathophysiology of coronary arteriovenous fistula and to propose potential treatment strategies. Methods:Eleven adult patients were treated surgically for coronary arteriovenous fistulas (8 male, 3 female) during the last three years. Mean age was 48,7 ± 9,5 years (range 32-65 years). Diagnosis was made by coronary angiography and transesophageal echocardiography Results: All patients were symptomatic due to the associating cardiac disorder or fistula. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
114
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 24 publications
3
114
0
3
Order By: Relevance
“…Some authors reported that surgical treatment is very effective and safe. 5,[16][17][18] The fi rst successful surgical closure was reported by Biorck et al 19 After that there have been many series published up to 56 cases. Overall, mortality is low (~1%); single ligation is common; excision of fi stula is rare; and cardiopulmonary bypass is used in approximately one-half of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported that surgical treatment is very effective and safe. 5,[16][17][18] The fi rst successful surgical closure was reported by Biorck et al 19 After that there have been many series published up to 56 cases. Overall, mortality is low (~1%); single ligation is common; excision of fi stula is rare; and cardiopulmonary bypass is used in approximately one-half of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…After the first decade, the frequency of both symptoms and complications increases. Complications include 'steal' from the adjacent myocardium causing myocardial ischemia, thrombosis, embolism, cardiac failure, atrial fibrillation, rupture, endocarditis/endarteritis and arrhythmias [1]. Clinical symptoms such as exertional angina or dyspnea are the primary indications for closure of a fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery fistula (CAF) are mostly abnormal congenital connections between a coronary artery and a cardiac or major intrathoracic vessel [1]. Coronary artery fistulas are rare with a 0.2% to 0.6% incidence in angiographic series.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, symptoms and complications are less common in young patients, but the risk increases with age as the fistula enlarges. This may eventually lead to severe complications: myocardial ischaemia sudden cardiac death, endocarditis or secondary aortic and mitral valves dysfunctions [1,4,13].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of this anomaly varies in literature, it is estimated that up to 0.4% of all congenital anomalies of the heart are CAF which are detected in up to 0.8% of patients undergoing coronary angiography [1,3,4,16].…”
Section: Introductionmentioning
confidence: 99%